2019
DOI: 10.1088/1402-4896/ab2d96
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of (4 + 4)-Kaluza–Klein type theory

Abstract: We develop a type of Kaluza-Klein formalism in (4 + 4)-dimensions. In the framework of this formalism we obtain a new kind of Schwarzschild metric solutions that via Kruskal-Szequeres can be interpreted as mirror black and white holes. We found that this new type of mirror black and white holes solutions in (3 + 1)-dimensions support the idea that the original space-time can be extended to (4 + 4)-signature. Using octonions, we also discus linearized gravity in (4 + 4)-dimensions.On the other hand, it is well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…First, the Dirac equation in (4 + 4)-dimensions is consistent with Majorana-Weyl spinors which give exactly the same number of components as the complex spinor of 1/2spin particles such as the electron or quarks [6,7]. Second, the most general Kruskal-Szekeres transformation of a blackhole coordinates in (1+3)-dimensions leads to 8-regions (instead of the usual 4-regions), which can be better described in (4 + 4)-dimensions [8]. Third, loop quantum gravity in (4 + 4)-dimensions [9-10] admits a self-duality curvature structure analogue to the traditional (1 + 3)-dimensions.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…First, the Dirac equation in (4 + 4)-dimensions is consistent with Majorana-Weyl spinors which give exactly the same number of components as the complex spinor of 1/2spin particles such as the electron or quarks [6,7]. Second, the most general Kruskal-Szekeres transformation of a blackhole coordinates in (1+3)-dimensions leads to 8-regions (instead of the usual 4-regions), which can be better described in (4 + 4)-dimensions [8]. Third, loop quantum gravity in (4 + 4)-dimensions [9-10] admits a self-duality curvature structure analogue to the traditional (1 + 3)-dimensions.…”
Section: Introductionsupporting
confidence: 55%
“…First, it may be interesting to consider a generalized Kruskal-Szekeres transform of the line element (32). This must lead to a connection with the observation [8] that in the (4 + 4)-world such a transform implies 8-regions instead of the usual 4-regions. Second, since it has been shown that in (4 + 4)-dimensions there exist a kind of duality of the cosmological constant one wonders what is the relation of such a duality with dual black-hole solution developed in this work (see Ref.…”
Section: Final Remarksmentioning
confidence: 84%
“…[12,27]). Second, the most general Kruskal-Szekeres transformation of a black-hole coordinates in 1 þ 3 ðÞ -dimensions leads to eightregions (instead of the usual four-regions), which can be better described in 4 þ 4 ðÞdimensions [28]. Third, it also has been shown [29] that duality…”
Section: Final Remarksmentioning
confidence: 99%
“…Note that the reason to write the quantum operators ε and ˆµ  in terms of P l rather than  can be traced back to the geodesic Equation (4) which is independent of the test particle mass and therefore the quantities ε and σ  that play the analo-gue role of energy and momentum, are dimensionless. Thus, the formula (7) leads to the Schrödinger equation…”
Section: Quantization; Zero-point "Energy"mentioning
confidence: 99%
“…Second, in Ref. [7] it has been shown that a general Kruskal-Szekeres transform, in black-hole physics, implies 8 hidden regions instead of just 4-regions as it is usually believed. It turns out that this 8-regions admit better interpretation in a world of (4 + 4)-dimensions.…”
Section: Introductionmentioning
confidence: 96%